2022
DOI: 10.3233/ies-210215
|View full text |Cite
|
Sign up to set email alerts
|

Variations in upper limb and trunk muscles activation during isometric exercises with or without exertion of control

Abstract: BACKGROUND: Muscle activation during isometric contraction can be changed using an external-focus instruction method. OBJECTIVE: To explore and compare the activity of eight upper limb and trunk muscles during isometric chest squeeze exercises, performed in the same posture with and without the exertion of control to avoid crushing an object. METHODS: Muscle activation by an isometric chest squeeze with 45∘ shoulder abduction and forearm pronation was examined. Isometric chest squeeze exercises were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In this study, a side plank exercise was performed using a paper balloon while exerting control not to crush the item. In a previous study, Murofushi et al demonstrated externally focused instruction while exerting control to avoid crushing an item maintaining a static position and holding a soft paper balloon during a chest squeeze exercise [8]. This method significantly activated the LT without involving any complicated movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, a side plank exercise was performed using a paper balloon while exerting control not to crush the item. In a previous study, Murofushi et al demonstrated externally focused instruction while exerting control to avoid crushing an item maintaining a static position and holding a soft paper balloon during a chest squeeze exercise [8]. This method significantly activated the LT without involving any complicated movement.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore agonist and antagonist muscle cocontractions were found between LT and UT, Lat and PM. The greater the force exerted by the agonist muscles, the more the appropriate amount of contraction of the antagonist muscle is required to maintain the posture and joint angle [8]. Previous studies have reported that a collection of trunk muscles work synchronously to maintain and stabilize posture [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that the elderly population continues to increase [ 27 ], health maintenance and physical independence in this population is a global goal [ 28 ]. Fatigue and pain are the major symptoms in this population [ 5 ], and isometric activity can be an important strategy for recreational, sports, and rehabilitation plans to improve health, fitness, and functional performance, since its benefits include improved joint stability (without joint movement), lower blood pressure [ 29 , 30 ] and decreased overall pain [ 31 ].…”
Section: Introductionmentioning
confidence: 99%